Strengthening Religious Moderation through Pioneer Orientation for West Kalimantan Religious Leaders - Kurniawan, Syamsul; Hidayat, Samsul (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article aims to provide an overview of pioneer orientation initiatives designed to promote religious moderation among religious leaders in West Kalimantan, organized by the Regional Office of West Kalimantan’s Ministry of Religious Affairs. The content of this article is derived from our community engagement activities at Hall 2 of the Asrama Haji [Hajj Dormitory]. The importance of strengthening religious moderation among religious leaders in West Kalimantan cannot be overstated, given their crucial role in promoting religious harmony. This reinforcement is achieved through pioneer orientation activities aimed at preparing religious leaders to incorporate religious moderation into their daily practices within the community. The material for these pioneer orientation activities to strengthen religious moderation is provided using the discovery learning model. This model maximizes participants' ability to systematically, critically, and logically explore and investigate, allowing them to independently acquire the knowledge, attitudes, and skills required for religious moderation within the context of their roles. The desired outcome is a tangible change in behavior. An analysis of the pretest and posttest results, as well as the assessment process that we conducted reveals a significant increase in knowledge, accompanied by shifts in attitudes and behavior of religious leaders towards a more moderate approach.